HUMAN CHARACTERISTICS AND COUNSELING - Andika Fawri; Yeni Karneli; Prayitno Prayitno (Literasi Nusantara, 2021)
Law on the national education system Law No. 20/2003 article 1 paragraph (1) "Education is a conscious and planned effort to create an atmosphere of learning and the learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble character and skills needed by him, the people of the nation and the state. The counselor is one of the educators with the aim of achieving the meaning of education. Human dignity can be increased by the development of the content contained in it. And counselors assist in linking individuals who have influence on their HMM content by using service delivery and support activities. The development of the HMM content in individuals so that it is able to make individuals have good spirit energy in themselves.